A novel role for an APC2-Diaphanous complex in regulating actin organization in Drosophila. - Webb, R.L.; Zhou, M.N.; McCartney, B.M. (Development, 2009)
The rearrangement of cytoskeletal elements is essential for many cellular processes. The tumor suppressor Adenomatous polyposis coli (APC) affects the function of microtubules and actin, but the mechanisms by which it does so are not well understood. Here we report that Drosophila syncytial embryos null for Apc2 display defects in the formation and extension of pseudocleavage furrows, which are cortical actin structures important for mitotic fidelity in early embryos. Furthermore, we show that the formin Diaphanous (DIA) functions with APC2 in this process. Colocalization of APC2 and DIA peaks during furrow extension, and localization of APC2 to furrows is DIA-dependent. Furthermore, APC2 binds DIA directly through a region of APC2 not previously shown to interact with DIA-related formins. Consistent with these results, reduction of dia enhances actin defects in Apc2 mutant embryos. Thus, an APC2-DIA complex appears crucial for actin furrow extension in the syncytial embryo. Interestingly, EB1, a microtubule +TIP and reported partner of vertebrate APC and DIA1, may not function with APC2 and DIA in furrow extension. Finally, whereas DIA-related formins are activated by Rho family GTPases, our data suggest that the APC2-DIA complex might be independent of RHOGEF2 and RHO1. Furthermore, although microtubules play a role in furrow extension, our analysis suggests that APC2 and DIA function in a novel complex that affects actin directly, rather than through an effect on microtubules.